Increased expression of phospholipase Dα1 in guard cells decreases water loss with improved seed production under drought in Brassica napus. Issue 3 (29th December 2012) - Lu, Shaoping; Bahn, Sung C.; Qu, Gang; Qin, Haiying; Hong, Yue; Xu, Qingpeng; Zhou, Yongming; Hong, Yueyun; Wang, Xuemin
Summary The activation of phospholipase Dα1 (PLDα1) produces lipid messenger phosphatidic acid and promotes stomatal closure in Arabidopsis. To explore the use of the PLDα1‐mediated signalling towards decreasing water loss in crop plants, we introduced Arabidopsis PLDα1 under the control of a guard cell–specific promoter AtKatIpro into two canola (Brassica napus) cultivars. Multiple AtKatIpro::PLDα1 lines in each cultivar displayed decreased water loss and improved biomass accumulation under hyperosmotic stress conditions, including drought and high salinity. Moreover, AtKatIpro::PLDα1 plants produced more seeds than did WT plants in fields under drought. The results indicate that the guard cell–specific expression of PLDα1 has the potential to improve crop yield by enhancing drought tolerance.